FALLS FROM BUILDINGS IN THE PAEDIATRIC POPULATION. Issue 12 (18th November 2016) - Haq, H; Fanous, R; Clark, M; Parikh, A
Abstract : Objectives & Background: Approximately 4, 000 children under the age of 15 are injured falling from windows in the UK. Ten of the children die and an unknown number suffer serious injuries. This study highlights a number of temporal, demographic and socio-economic risk factors for this mechanism of injury. The study also identifies potential strategies to reduce the number of falls from windows. Methods: This retrospective study of paediatric patients utilised the Barts Health Trust Paediatric Trauma database. Initially, all patients under 16 years of age, who presented with a fall from a height (window, roof or balcony) between 2010 and 2015 were included. This was followed by a short phone survey that was conducted to find out more about safety measures at the location and housing circumstances. Results: 93 patients presented with falls from a height during the study period. Two (2.15%) of these children died. Boys were twice as likely as girls to fall and 88 (94.6%) were accidents. There was a seasonal pattern with 61% of falls occurring in the summer months. 78 (83.87%) of children with falls from buildings required admission to hospital, with a mean length of stay of 3.37 days. 10.5% of children required admission to the Paediatric Critical Care Unit and 11% required emergency surgery. 53% of patients sustained limb fractures and 42% head injuries. 12% of those patients contacted by telephone survey were experiencing long term health problems. The majority (72.5%) of falls occurred in neighbourhoods ranked within the 30% most deprived in the country. Only 12% of the households represented in this study had functioning safety locks. 12% of those children who fell from windows had a pre-existing diagnosis of autism. Conclusion: This study quantifies the impact the falling from windows had on individual children, their families and the broader healthcare system. This study also suggest that window locks are extremely effective at reducing falls and should be evaluated as a public health intervention. Furthermore, the disproportionately high number of autistic child that falls from windows should prompt an urgent review to ensure these vulnerable children are living in a safe environment.